نظرية التعدد الصوتي في البلاغة الجديدة (اوزفالدو ديكرو أنموذجا) - عبد الله شلاهي فالح; ال صوينت مؤيد (Journal of College of Education, 2020)
This study seeks the contribution to the theoretical field at the subject of polyphonie. It takes Ducrot as a model in accordance with his movement and development at the polyphonie concept. This movement is closely related to Bakhtine for a long period of time. Also, it was deeply worked at the literary field. Ducrot is worked to draw this thema to the pragmatic field. So, Ducrot’s interest in polyphonie has come into play at the language system. He is examined the various linguistic structures of the polyphonie at the level of the vocals. Therefore, Ducrot’s view is departed from Bakhtine in his linguistic vision as well as the former’s novelty. Ducrot is added, at his novelty aspect, the viewpoint at the polyphonie issue via his rejection of the personal presence of the polyphonie to achieve the diversity. So, Ducrot’s novelty is the self-talk which is divided at the vocal level of oneself into a speaker and vocalizers. Thus, Ducrot contributes to the establishment of pragmatic polyphonie besides its literary one.